The Dutch Deposit of Electronic Publications (DNEP) - 1995-2000 - Sijtsma, Lex (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2001)
In 1993 the Internet took off with the introduction of HTML and the first browser (Mosaic). Two years later, in 1995, the Koninklijke Bibliotheek (KB) decided to start a series of experiments and projects which would lead to a deposit system for Dutch Electronic Publications. In the same year the KB made a policy decision to include electronic material into its deposit. That marked the start of the Dutch Deposit for Electronic Publications (DNEP). Both as an operational service and at the same time as a test-bed for research into digital archiving. Early 1999 a Request For Information (RFI) was sent out to selected companies. This was done to establish whether the functionalities the KB deemed neccessary for a digital deposit were available in the marketplace. On the basis of the positive outcome of this Request a European Tender was started. The KB developed a process model for a digital deposit as well as detailed functional requirements for such a system. A supplier, IBM, was selected. At the moment (early June 2000) talks about the implementation are in progress. The project will start in the summer of start of autumn of 2000 and will take 24 months. The Dutch government has acknowledged that the establishment of the Dutch electronic bibliography and the DNEP itself are indeed tasks of the Koninklijke Bibliotheek. We expect that appropriate structural funding to supports these tasks will become available. In this paper an overview is given of what the KB has done since 1995 up till now and how this has led to the implementation-project that is about to start.